2016
DOI: 10.1111/1742-6723.12586
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of pain in children treated by paramedics

Abstract: Disparities in analgesic administration based on age and the low rate of pain scores documented in very young children identified in the present study should inform strategies that aim to improve the assessment and management of pain in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 34 publications
0
49
0
Order By: Relevance
“…Effective pain management consists of pharmacological and non-pharmacological interventions (Joint Royal Colleges Ambulance Liaison Committee and Association of Ambulance Chief Executives, 2019). Analgesic administration rates for pre-hospital children suffering from acute pain have been low (Lerner et al, 2014;Lord et al, 2016;Whitley and Bath-Hextall, 2017). For example one Australian study (Lord et al, 2016) found that more than half (55%) of children with severe pain (verbal numeric rating scale 8-10) did not receive any analgesics.…”
Section: Introductionmentioning
confidence: 99%
“…Effective pain management consists of pharmacological and non-pharmacological interventions (Joint Royal Colleges Ambulance Liaison Committee and Association of Ambulance Chief Executives, 2019). Analgesic administration rates for pre-hospital children suffering from acute pain have been low (Lerner et al, 2014;Lord et al, 2016;Whitley and Bath-Hextall, 2017). For example one Australian study (Lord et al, 2016) found that more than half (55%) of children with severe pain (verbal numeric rating scale 8-10) did not receive any analgesics.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer than half of such patients receive analgesia from paramedics1113 or within 1 hour of arrival at the ED 14. Younger patients are less likely to have a documented assessment of pain intensity or receive adequate pain medication 11,12,14. Even when analgesia is provided, pediatric patients are frequently under-dosed15 and only a small proportion achieve adequate pain relief 14.…”
Section: Introductionmentioning
confidence: 99%
“…Despite pain being a key research priority in paediatric emergency care, 1,2 oligoanalgesia is frequently reported. Studies of children with severe trauma-related pain reveal that fewer than half receive analgesia from paramedics, [3][4][5] or within 1 h of arriving at the emergency department (ED). 6 Many children undergoing painful hospital procedures receive no analgesia, and younger children receive disproportionately less analgesia than school-age counterparts.…”
Section: Introductionmentioning
confidence: 99%